Challenges and possibilities for environmentally sound recycling of ships and composite boats in European union - Premur, Vitomir (Array, 2019)
In this paper are presented challenges that countries of European Union face when recycling ships and composite boats. European ship owners control over 40 % of the world’s merchant ship fleet, with Greece as the top ship-owning country globally. Nowadays, ship recycling is being regulated and positive progression was made towards it since steel industry belongs in world’s top five and stable market and makes recycling of scrap metals from ships attractive. On the other hand, yachts, sailing boats and small boats are mainly made from composite materials because of their favourable properties, making them great investment, but end-of-life management is more complicated and not quite regulated by the law yet. Unlike commercially oriented ships, which are constantly in move and disposed when the maintenance costs of the vessel start to exceed possible revenue, old boats for recreational and tourism-oriented purposes most rarely move. Hundreds of thousands lie in marinas and are abandoned due to the maintenance costs thus discouraging the owners from keeping it. Hence, a growing number of marinas worldwide will have the problem of boat disposal in a sustainable way in the future. In this paper is given short summary on waste ships and boats management issues.